Do Students' Learning Outcomes in Mathematics Change Depending on The Availability of Learning Facilities - Radhitya Duta Pradana; Endrayana Putut Laksminto Emanuel; Christi Matitaputty; Wahyuningtyas Puspitorini (International Journal of Studies in International Education, 2025)
The purpose of this quantitative descriptive study is to ascertain how students' learning outcomes in mathematics are impacted by the availability of learning facilities. In order to increase learning outcomes, the teaching and learning process will be more successful if supported by sufficient facilities, such as proper study tables, additional illumination sources, lighting indications throughout the house, appropriate study chairs, appropriate bookcases, availability of math textbooks and worksheet books, internet access at home, sufficient cell phones, student-owned question banks, and internet use can all support learning activities. Thirty students in all took part, and checklists, questionnaires, and documentation were the instruments utilized to collect data. Descriptive analysis of the learning outcome variable data revealed that 20 students in class XI, or 67.67%, finished with a Minimum Passed Value of 80, whereas 10 students, or 33.33%, were incomplete. Using SPSS, a straightforward linear regression calculation method yielded the following results: Y = 98,793 + 0,590X. The findings of the study demonstrate that student learning outcomes are influenced by the accessibility of learning facilities. For additional study, you can focus on variables other than the availability of learning facilities that affect student learning results.